2020
DOI: 10.1016/j.neunet.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Chimera states in hybrid coupled neuron populations

Abstract: Here we study the emergence of chimera states, a recently reported phenomenon referring to the coexistence of synchronized and unsynchronized dynamical units, in a population of Morris-Lecar neurons which are coupled by both electrical and chemical synapses, constituting a hybrid synaptic architecture, as in actual brain connectivity. This scheme consists of a nonlocal network where the nearest neighbor neurons are coupled by electrical synapses, while the synapses from more distant neurons are of the chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…In addition, our mind is so dynamic and adaptive that, not only does it generate new information FIGURE 5 | (Left) Network architecture used for the study of the emergence of chimera behavior using nearest neighbor electrical connections (solid lines) and long-range chemical synapses (dashed lines). (Right) Density plot depicting the time-dependent voltage traces of a 1,000 neuron population interconnected with the topology in the left panel (Calim et al, 2020). This shows the emergence of two chimeras separating different neuron subpopulations with different dynamical regimes, one (the center of the image) with high-amplitude normal spiking activity and the others (the non-centered regions) with high-voltage low amplitude oscillations, constituting a so-called chaotic amplitude chimera (Calim et al, 2020).…”
Section: Discussion and Perspectivesmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, our mind is so dynamic and adaptive that, not only does it generate new information FIGURE 5 | (Left) Network architecture used for the study of the emergence of chimera behavior using nearest neighbor electrical connections (solid lines) and long-range chemical synapses (dashed lines). (Right) Density plot depicting the time-dependent voltage traces of a 1,000 neuron population interconnected with the topology in the left panel (Calim et al, 2020). This shows the emergence of two chimeras separating different neuron subpopulations with different dynamical regimes, one (the center of the image) with high-amplitude normal spiking activity and the others (the non-centered regions) with high-voltage low amplitude oscillations, constituting a so-called chaotic amplitude chimera (Calim et al, 2020).…”
Section: Discussion and Perspectivesmentioning
confidence: 98%
“…(Right) Density plot depicting the time-dependent voltage traces of a 1,000 neuron population interconnected with the topology in the left panel (Calim et al, 2020). This shows the emergence of two chimeras separating different neuron subpopulations with different dynamical regimes, one (the center of the image) with high-amplitude normal spiking activity and the others (the non-centered regions) with high-voltage low amplitude oscillations, constituting a so-called chaotic amplitude chimera (Calim et al, 2020). Voltage membrane dynamics of the neurons (purple circles in the right panel) has been computed using a Morris-Lecar neuron model (Morris and Lecar, 1981).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, and in the years to follow, it was shown that chimeras can be implemented in experimental setups (e.g., Hagerstrom et al, 2012;Tinsley et al, 2012;Totz et al, 2018;Ebrahimzadeh et al, 2020;Gambuzza et al, 2020), providing first evidence that chimera states do not only exist in mathematical models but can also play a role in real-world dynamics. In parallel, various conceptual links were established between chimeras and a variety of natural and man-made networks outside of experimental labs (e.g., Sakaguchi, 2006;Abrams et al, 2008;Ramlow et al, 2019;Calim et al, 2020;Gerster et al, 2020;Rontogiannis and Provata, 2021). Furthermore, approaches to control chimeras were developed (e.g., Sieber et al, 2014;Bick and Martens, 2015;Omelchenko et al, 2018;Ruzzene et al, 2019;Ruzzene et al, 2020;Vadivasova et al, 2020;Zhang and Dai, 2022).…”
Section: Chimera Statesmentioning
confidence: 99%
“…Therefore, recent work dealt with interactions of chimera states across coupled layers in multilayer networks (e.g., Majhi et al, 2016;Maksimenko et al, 2016;Andrzejak et al, 2017;Andrzejak et al, 2018;Sawicki et al, 2019;Ruzzene et al, 2020;Vadivasova et al, 2020;Rontogiannis and Provata, 2021;Chen et al, 2022). Moreover, various neuron models were used instead of the simple phase oscillators as network nodes (e.g., Sakaguchi, 2006;Hizanidis et al, 2014;Hizanidis et al, 2016;Santos et al, 2017;Chouzouris et al, 2018;Calim et al, 2020;Gerster et al, 2020;Provata and Venetis, 2020;Glaze and Bahar, 2021;Rontogiannis and Provata, 2021;Simo et al, 2021;Zhang and Dai, 2022). In addition, either experimentally obtained real brain connectivity data (e.g., Hizanidis et al, 2016;Santos et al, 2017;Chouzouris et al, 2018;Bansal et al, 2019;Ramlow et al, 2019;Gerster et al, 2020) or basic neuronal connectivity principles (e.g., Rontogiannis and Provata, 2021;Zhang and Dai, 2022) were used to design mathematical model networks capable to show chimera states.…”
Section: Chimera Statesmentioning
confidence: 99%